2019
DOI: 10.1016/j.foodhyd.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Zinc bioaccessibility is affected by the presence of calcium ions and degree of methylesterification in pectin-based model systems

Abstract: Minerals are required by the human body to perform physiological functions. Mineral deficiencies, often caused by low mineral bioaccessibility in plant-based foods, are a matter of great concern all over the world. Several antinutrients (e.g. pectin) may contribute to this reduced mineral bioaccessibility by formation of indigestible complexes due to mineral binding. Structural characteristics of the antinutrients, as for instance the degree of methylesterification (DM) in the case of pectin, may play a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…43 While these have different abilities for binding minerals, different minerals bind to varying extents to one antinutrient as well. 44 Typically, Fe is known to be strongly chelated to phytic acid in legumes and cereal seeds. 12 Based on our observations discussed above, it was found that Mg and Zn seem to be relatively loosely bound to antinutrients in milled Bambara groundnuts, given their ease of solubility.…”
Section: Papermentioning
confidence: 99%
“…43 While these have different abilities for binding minerals, different minerals bind to varying extents to one antinutrient as well. 44 Typically, Fe is known to be strongly chelated to phytic acid in legumes and cereal seeds. 12 Based on our observations discussed above, it was found that Mg and Zn seem to be relatively loosely bound to antinutrients in milled Bambara groundnuts, given their ease of solubility.…”
Section: Papermentioning
confidence: 99%
“…However, the study of the bioaccessibility as well as bioavailability of these incorporated extracts is of paramount importance. Bioaccessibility refers to the fraction of nutrient released from the food matrix into the gastrointestinal tract after digestion which becomes available for absorption through the intestine (Rousseau et al ., 2019). Bioavailability refers to the quantity of nutrient that has been digested as well as absorbed and then available for the metabolic functions (Bosscher et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we did not investigate the binding effect of the enzymes and bile salts individually, as such it was not possible to determine whether the binding effect was from specific enzymes or bile salts or their combination. Although Rousseau et al (2019) found a zinc binding effect from bile salts and not from enzymes, they used different enzymes to ours such that an enzyme binding effect cannot be ruled out, especially from pancreatin which was particularly difficult to dissolve. The iron and zinc binders present in the reagent blank are most likely associated with the pancreatin and bile considering their high iron and zinc contribution to the gastrointestinal digesta.…”
Section: Effect Of Reagents and Sample Matrix On Solubility Of Iron A...mentioning
confidence: 90%
“…Saturated solutions of pancreatin and bile are used in the INFOGEST method as is, and these precipitate during centrifugation with the potential to adsorb metals into the solid phase. Rousseau et al (2019), showed that zinc bioaccessibility was drastically reduced when the complexity of the in vitro digestion model was increased by adding bile salts in comparison to enzymes which had no effect. They concluded that bile salts may interact with zinc thereby reducing zinc bioaccessibility.…”
Section: Infogest Methodsmentioning
confidence: 99%